The Immediate Effects of Conventional and High-Power Pain Threshold Ultrasound on Myofascial Pain Syndrome among Young Thai Adults - Manorangsan, Sukwida (Science & Technology Asia, 2024)
The study aimed to compare the immediate effects of conventional ultrasound (Con-US) and high-power pain threshold ultrasound (HPPT-US) on pain and neck range of motion (ROM) in young Thai adults with active trigger points of myofascial pain syndrome (MPS). Sixty participants were randomly allocated into two groups: Con-US (mean age 20.97±1.16 years) and HPPT-US (mean age 21.47±1.28 years). Each group underwent a single ultrasound session lasting 5 minutes. Parameters assessed pre- and post-treatment included pain intensity, neck ROM, pressure pain threshold (PPT), and pressure pain tolerance (PPTo). The average intensity dose for Con-US was 1.0 W/cm2, while for HPPT-US it was 0.83 W/cm2. Both techniques improved pain parameters, but there was no significant interactive effect between group and time. The single moderate-intensity session of HPPT-US may not have a lasting impact on pain tolerance due to the lack of a cumulative effect. Further studies with increased treatment sessions and higher intensity ultrasound are recommended.